2011
DOI: 10.1097/olq.0b013e3182260987
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Dual Non-Treponemal/Treponemal Syphilis Point-of-Care Test to Prevent Adverse Pregnancy Outcomes in Sub-Saharan Africa

Abstract: The dual-POC test may help save cost in resource-poor settings where disease prevalence (and loss to follow-up) is high, while substantially reducing overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 28 publications
1
104
0
Order By: Relevance
“…All of these previously published estimates fall within the bounds of our 95% confidence intervals. More recent analyses that evaluated the cost-effectiveness of antenatal syphilis screening using the ICS test are available for Tanzania (ICER: US$12–US$17 [34]) and for SSA in general [7],[35]. The studies for SSA found that screening was cost-saving, e.g., it was associated with lower cost as well as improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these previously published estimates fall within the bounds of our 95% confidence intervals. More recent analyses that evaluated the cost-effectiveness of antenatal syphilis screening using the ICS test are available for Tanzania (ICER: US$12–US$17 [34]) and for SSA in general [7],[35]. The studies for SSA found that screening was cost-saving, e.g., it was associated with lower cost as well as improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, antibiotic therapy may also reduce the incidence of other relevant clinical end points such as miscarriage, spontaneous abortion, or low birth weight, which are not included in our model. Third, unlike other studies published in the relevant literature [7],[35], we did not model lifetime treatment costs associated with congenital syphilis. Infants born with congenital syphilis may experience complications of the disease that can result in increased direct medical costs over their lifetime, in which case screening may partially offset these costs or even result in a net cost saving.…”
Section: Discussionmentioning
confidence: 99%
“…Owusu-Edesei and colleagues recently reported that a screening strategy employing an ICS TT cost less than a dual-POCT (TT and NTT) strategy in a high-prevalence setting but that the dual-POCT strategy may significantly reduce overtreatment (68). No cost-effectiveness data are available for developed countries.…”
Section: Poctmentioning
confidence: 99%
“…10,11 Since then, newer, rapid and affordable POCTs for syphilis have become available and are in use in several developing countries. 12,13 The need to develop more POCTs for use in all settings, including the industrialised world, is an imperative. Though this need is recognised, perceptions of the qualities that describe the desired POCTs for STIs differ between frontline clinicians and the industry professionals who are charged with developing and marketing these tests.…”
Section: Introductionmentioning
confidence: 99%